A Study on the Mechanism of Tutor Guidance on Scientific Research Ability of Undergraduates in Application-oriented Universities—Based on the Mediating Effect of Research Efficacy - Zhao, Yanting (The education review, USA, 2025)
Scientific research training is a key path to cultivating the practical innovation ability of undergraduates in application-oriented universities, and tutor guidance is its core practice form. Based on the theory of situated learning, this study investigated 723 undergraduates from 3 application-oriented universities. The results show that students who received tutor guidance significantly outperformed those who did not in scientific research ability indicators. After controlling variables such as gender, grade, major, and academic performance, tutor guidance had a positive impact on the scientific research ability of undergraduates in applicationoriented universities, among which the three dimensions of guidance frequency, guidance method, and guidance content all showed significant positive effects. Research efficacy played a mediating role in the relationship between tutor guidance and scientific research ability. Further analysis showed that factors such as students' individual characteristics (such as research motivation and professional foundation), universities' scientific research environment (such as laboratory sources and cooperation platforms), and institutional support (such as scientific research incentive policies) also significantly moderated or mediated this influence path. The research results have theoretical reference and practical guidance value for application-oriented universities to optimize the tutor guidance system and cultivate practical innovative talents.